Foreign element doping and thermal stability of alumina aerogels. Issue 3 (19th November 2021) - Peng, Fei; Jiang, Yonggang; Feng, Jian; Feng, Junzong; Li, Liangjun
Abstract: The addition of foreign elements is considered as an effective method to improve the thermal stability of alumina aerogels at a higher temperature. However, the location and stabilizing mechanism of the foreign elements in the alumina aerogel have not been carefully studied. In this work, Si or La was introduced into the network of alumina aerogels through a sol‐gel strategy. The Si‐doped alumina aerogel maintained high surface area (92 m 2 /g) and pore volume (0.572 cm 3 /g) even at 1300°C. The dopants prevented α‐Al2 O3 transformation at elevated temperatures (1200°C–1300°C). The distribution of foreign ions and their stabilizing mechanism were discussed in detail. The doped alumina aerogels reinforced by mullite fiber felt, with quite low density and thermal conductivity, can be used as high‐temperature thermal insulations.